Identification of Novel Raft Marker Protein, FlotP in Bacillus anthracis - Somani, Vikas K.; Aggarwal, Somya; Singh, Damini; Prasad, Tulika; Bhatnagar, Rakesh (Frontiers in Microbiology, 2016)
Lipid rafts are dynamic, nanoscale assemblies of specific proteins and lipids, distributed heterogeneously on eukaryotic membrane. Flotillin-1, a conserved eukaryotic raft marker protein (RMP) harbor SPFH (Stomatin, Prohibitin, Flotillin, and HflK/C) and oligomerization domains to regulate various cellular processes through its interactions with other signaling or transport proteins. Rafts were thought to be absent in prokaryotes hitherto, but recent report of its presence and significance in physiology of Bacillus subtilis prompted us to investigate the same in pathogenic bacteria (PB) also. In prokaryotes, proteins of SPFH2a subfamily show highest identity to SPFH domain of Flotillin-1. Moreover, bacterial genome organization revealed that Flotillin homologue harbouring SPFH2a domain exists in an operon with an upstream gene containing NFeD domain. Here, presence of RMP in PB was initially investigated in silico by analyzing the presence of SPFH2a, oligomerization domains in the concerned gene and NfeD domain in the adjacent upstream gene. After investigating 300 PB, 4 were found to harbor RMP. Among them, domains of Bas0525 (FlotP) of Bacillus anthracis (BA) showed highest identity with characteristic domains of RMP. Considering the global threat of BA as the bioterror agent, it was selected as a model for further in vitro characterization of rafts in PB. In silico and in vitro analysis showed significant similarity of FlotP with numerous attributes of Flotillin-1. Its punctate distribution on membrane with exclusive localization in detergent resistant membrane fraction; strongly favors presence of raft with RMP FlotP in BA. Furthermore, significant effect of Zaragozic acid (ZA), a raft associated lipid biosynthesis inhibitor, on several patho-physiological attributes of BA such as growth, morphology, membrane rigidity etc., were also observed. Specifically, a considerable decrease in membrane rigidity, strongly recommended presence of an unknown raft associated lipid molecule on membrane of BA. In addition, treatment with ZA decreased secretion of anthrax toxins and FlotP expression, suggesting potential role of raft in pathogenesis and physiology of BA. Thus, the present study not only suggest the existence and role of raft like entity in pathophysiology of BA but also its possible use for the development of novel drugs or vaccines against anthrax.